PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BIOLOGI DILENGKAPI MIND MAP PADA MATERI POKOK SISTEM RESPIRASI UNTUK SMA - Sari, Witria Malra; Fifendy, Mades; Fadilah, Muhyiatul (Pendidikan Biologi, 2013)
ABSTRACT The purpose of this study to generate worksheets include material mind map on the respiratory system are valid and practical. This research is a development reseach, using a 4- D model of development. The model consists of four stages, are define, Design, Develop, and Disseminate, but this study is limited to the stage of develop. Tests conducted to 29 students of class XI SMA PGRI IPA4 1 Padang. The results obtained inform the validation value by88% with very valid category, while the value of 88% and the practicalities of studentteachers practicalities of 96%, which indicates a very practical category. LKS equipped biology mind map on the respiratory system of the material generated to obtain valid results and practical, it can be used as teaching materials in the learning process at school.